BCL-2 family of proteins and cell cycle regulatory genes play a role in the regulation of apoptosis induced by lithium and calyculin-A in HL-60 cells - Tshabalala, Nkhensani Cecilia (University of Limpopo (Turfloop Campus), 2007)
The biochemical mechanism of apoptosis induced by lithium remains unclear, although there is evidence suggesting the involvement of Bax and Bcl-2. Bcl-2 family of proteins play a critical role in the regulation of apoptosis in various tumour cell lines. This pathway may be altered in cancer cells. We have used calyculin-A (CL-A), an inhibitor of protein phosphatase 2A (PP2A), to investigate the mechanism by which lithium induces apoptosis in HL-60 cells. Previous studies in our laboratory established that lithium induces apoptosis of HL-60 cells at 10 mM and above; while CL-A induces apoptosis at 1 nM and above. The observed apoptotic effects were additive. These observations led to the hypothesis that lithium and CL-A exert their biological effects by acting on a similar target. It was, therefore, the aim of this study to establish whether lithium would also exert similar inhibitory effects on the apoptotic and cell cycle regulatory genes. We further aimed at delineating the effects of both lithium and CL-A on the expression profiles of apoptotic and cell cycle regulatory genes. In this study, HL-60 cells were treated with lithium, CL-A and the combination of both. This was followed by the assessment of cell proliferation and viability at specific time points, using Coulter Counter and trypan blue dye exclusion assay, respectively. Concentrations of lithium at 10 mM and 20 mM were found to inhibit cell proliferation and exerted modest effects on cell viability in a time- and dose-dependent manner. Likewise, CL-A inhibited cell proliferation and viability in a time- and dose-dependent fashion. The combination of lithium and CL-A showed additive inhibitory effects on the growth of HL-60 cells. Further, semi-quantitative RT-PCR analyses of apoptotic (bax and bcl-2) and cell cycle regulatory genes (cdc2 and cyclin-B1) were determined. Our data revealed an under-expression of bcl-2 mRNA and an up-regulation of bax mRNA in HL-60 cells treated with lithium, CL-A and the combination of both. In addition, the expression levels of cdc2 mRNA remained constant, while cyclin-B1 mRNA expression levels were up-regulated after 24 h in HL-60 cells that were treated with cytotoxic concentrations of lithium and CL-A alone. Furthermore, the combination of lithium and CL-A showed an up-regulation of cyclin-B1 mRNA while cdc2 mRNA levels remained constant in both treated and untreated HL-60 cells. To corroborate the RT-PCR data, we present evidence by Western blot analysis that Bcl-2 family of proteins and cell cycle regulatory genes indeed play a critical role in the regulation of apoptosis in HL-60 cells. Western blot analysis revealed a down-regulation of Bcl-2 under all treatment conditions. However, lithium and CL-A alone failed to show any detectable expression levels of both Bax and cyclin-B1 proteins. In contrast, the combination of both lithium and CL-A showed an up-regulation of Bax and Cdc2 proteins in HL-60 cells. These findings suggest that the molecular mechanism elicited by lithium, CL-A and the combination of both on the growth inhibition of HL-60 cells involves an aberrant expression of apoptotic and cell cycle regulatory genes. In addition, these observations may allude to a notion that both lithium and CL-A may be used and administered successfully as positive alternative anticancer drugs.
Thesis (M.Sc. (Chemistry)) --University of Limpopo, 2007
Keywords: Cell cycle; Apoptosis; Lithium; Calyculin-A; 546.381; Lithium